DETERMINANTS OF VILLAGE FUND MANAGEMENT - Rofifah Rahadatul Aisy; Rohmad Yuliantoro Catur Wibowo (JAT : Journal Of Accounting and Tax, 2026)
This study was designed to analyze the impact of accountability, transparency, and community participation on village fund management in Bantul Regency, Yogyakarta Special Region. This stems from the large allocation of the 2025 village fund budget, which exceeds Rp 121 billion and is distributed to 75 villages. This study aims to fill the empirical gap in the public financial governance literature. This study uses a quantitative, survey-based approach, with a purposive sampling technique. The data collection instrument was a questionnaire distributed to village officials. The results of multiple linear regression tests indicate that the accountability variable has no effect on village fund management. This condition suggests that the implementation of accountability still tends to be positioned as fulfilling administrative obligations, rather than as a substantive governance mechanism. Conversely, the transparency and community participation variables have been shown to have a positive effect on village fund management. This emphasizes the relevance of Stewardship Theory, which views village officials as stewards capable of aligning institutional goals with community interests through information transparency and active community involvement in all stages of village development.